Characterization and in vitro assessment of seaweed bioactives with potential to reduce methane production - Krizsan, Sophie J.; Hayes, Maria; Gröndahl, Fredrik; Ramin, Mohammad; O’Hara, Peter; Kenny, Owen (Frontiers in Animal Science, 2022)
This study collates compositional analysis of seaweeds data with information generated from in vitro gas production assays in the presence and absence of seaweeds. The aim was to assess and rank 27 native northern European seaweeds as potential feed ingredients for use to reduce methane emissions from ruminants. It provides information for use in future in vivo dietary trials concerning feed manipulation strategies to reduce CH4 emissions efficiently from domestic ruminants based on dietary seaweed supplementation. The seaweeds H. siliquosa and A. nodosum belonging to phylum Phaeophyta displayed the highest concentration of phlorotannins and antioxidant activity among the macroalgae giving anti-methanogenic effect in vitro, while this explanation was not valid for the observed reduction in methane when supplementing with C. filum and L. digitata in this study. D. carnosa and C. tenuicorne belonging to phylum Rhodophyta had the highest protein content among the macroalgae that reduced methane production in vitro. There were no obvious explanation from the compositional analysis conducted in this study to the reduced methane production in vitro when supplementing with U. lactuca belonging to phylum Chlorophyta. The strongest and most complete methane inhibition in vitro was observed when supplementing with Asparagopsis taxiformis that was used as a positive control in this study.